Enhancement of Excess Electron Transfer Efficiency in DNA Containing a Phenothiazine Donor and Multiple Stable Phenanthrenyl Base Pairs. Issue 35 (19th July 2013) - Roethlisberger, Pascal; Wojciechowski, Filip; Leumann, Christian J.
<x xml:space="preserve">Abstract</x> EET grown ohm: Excess electron transfer (EET) was observed within a DNA duplex containing π‐stacked phenothiazine as an electron donor, phenanthrenes as electron carriers and 5‐bromouracil as an electron trap. Increasing the number of phenanthrenyl base pairs increased EET efficiency.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>